INDOLE BUTIRAT ACID (IBA) INDUCES HIGH FREQUENCY MULTIPLICATION IN ENDANGERED TITAN ARUM (Amorphophallus titanum (Becc.)): AN APPROACH TO GERMPLASM CONSERVATION - Setiawan, Ryan Budi; Rozen, Nalwida; Purnama Sari, Indah (Indonesian Journal of Forestry Research, 2025)
Titan arum (Amorphophallus titanum (Becc.)) was an endemic flora found only on the island of Sumatra, listed as endangered and possessing the largest flower among 170 species of Amorphophallus. Conservation activities could benefit from the use of plant propagation through cuttings. The success of cuttings was determined by the concentration of plant growth regulators (PGR) to induce the formation of roots, corms, and shoots, making the study of PGR concentration important. This study aimed to find the best IBA concentration to induce roots, corms, and shoots in A. titanum. The research was conducted from February to October 2023. The study was designed based on a completely randomized design with treatments of IBA concentration consisting of 5 levels: 0, 5, 10, 15, and 20 mg L-1. The results showed that an IBA concentration of 15 mg L-1 produced the best survival percentage (100%), rooting percentage (93.33%), corm formation percentage (93.33%), shoot formation percentage (76.67%), and an average of 1.20 shoots per cutting on A. titanum petiole cuttings.